2006
DOI: 10.1007/s11205-006-9032-z
|View full text |Cite
|
Sign up to set email alerts
|

Leisure and quality of life in an international and multicultural context: what are major pathways linking leisure to quality of life?

Abstract: leisure, quality of life, culture, meaning, diversity, strength,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
1
27

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(177 citation statements)
references
References 76 publications
(92 reference statements)
10
139
1
27
Order By: Relevance
“…More leisure time means more time for relaxing, doing some hobbies, also for family and social life. Leisure time could create positive emotion which increases happiness (Iwasaki, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…More leisure time means more time for relaxing, doing some hobbies, also for family and social life. Leisure time could create positive emotion which increases happiness (Iwasaki, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these efforts have often been confounded by a lack of consensus concerning the definition of QOL and, consequently, the use of other terminology such as subjective quality of life (SQOL), life satisfaction, happiness, and well-being (Bramston et al, 2002). Contemporary definitions of QOL suggest that it is socially and culturally constructed and that QOL subsumes factors such as life satisfaction and happiness (Iwasaki, 2006). The World Health Organization (WHO, 1997) defined QOL as:…”
Section: Quality Of Life and Happinessmentioning
confidence: 99%
“…Many of the current conceptualizations of how leisure influences QOL and happiness have been limited because of the dominant Western perspectives found in the leisure and QOL research literature (Iwasaki, 2006). However, a multi-national study conducted by the WHO that included Westernized countries (e.g., United States, France) and East-Asian countries (e.g., Japan, Thailand) found that opportunities for and participation in leisure activities was a significant contributor to QOL (Iwasaki).…”
Section: Ethnicity Leisure Quality Of Life and Happinessmentioning
confidence: 99%
“…Silverstein and Parker (2002) argued on the contribution of Leisure to 'successful' old age, a finding supported by Dann (2001), Nimrod (2007), and Coleman and Iso-Ahola (1993). Iwasaki et al (2005), Iwasaki (2007), and Jeffrey and Dobos A substantial amount of work provides support for the need to have a separate Vacations domain in Quality of Life. For example, the desire to travel has been argued as a fundamental need, and viewed almost as a universal right (Urry, 1990;Urry, 1995).…”
Section: The Contribution Of Vacations To People's Quality Of Lifementioning
confidence: 96%